Forró ősz a hidegháborúban - Magyarország 1956-ban - Kóthy, Judit; Topits, Judit; Rainer M., László (Hungary : 1956-os Intézet, 2006)
This gap-filling documentary made by the '1956 Institute' (http://www.rev.hu/rev/), presents the history of the 1956 Hungarian Revolution in a global political context. It examines the processes leading to the status quo in the post-war era, the characteristics of the Cold War and the antecedents of the revolution both in Eastern-Central Europe and in Hungary. The film depicts foreign reactions as well as the political considerations and conduct of the Great Powers. Recently rediscovered contemporary news footage from American, French, German and Russian archives further enrich the visual content of this documentary.
Duration: 00:56:00
Verzio Film Festival Submission
Keywords: Documentary films